Substance P/ Neurokinin-1 Receptor, Trigeminal Ganglion, Latency, and Coronavirus Infection-Is There Any Link? - Mehboob, Riffat; Kurdi, Maher; Bamaga, Ahmed; Aldardeir, Njoud; Nasief, Hisham; Moshref, Leena H.; Alsinani, Taghreed; Rayes, Almotasimbellah O.; Jabbad, Reem H. (Frontiers in Medicine, 2021)
Novel severe acute respiratory syndrome coronavirus 2 infection (SARS-CoV-2) is an acute respiratory and infectious disease. This perspective aims to provide a basic understanding of the inflammation caused by SARS-CoV-2 and its relation to trigeminal ganglion (TG). Virus enters through the mucous membranes of the orofacial region and reach the TG where it resides and take control of its peptides including Substance P (SP). SP is the main neuropeptide, neuromodulator and neuro-hormone of TG, associated with nociception and inflammation under noxious stimulus. SP release is triggered and consequently, it affects the immune cells and blood vessels to release the mediators for inflammation. Hence, cytokine storm is initiated and cause respiratory distress, bronchoconstriction and death in complicated cases. Neurokinin-1 Receptor (NK-1R) is the receptor for SP and it’s antagonists along with glucocorticoids may be used to alleviate the symptoms and treat this infection by blocking this nociceptive pathway. SP is the main culprit seem to be involved in the triggering of inflammatory pathways in SARS-CoV-2 infection. It has direct association with cardiorespiratory rhythm, sleep-wake cycle, nociception, ventilatory responses and regulates many important physiological and pathological roles. Its over-secretion should be blocked by NK-1R antagonist. However, experimental work leading to clinical trials are mandatory for further confirmation. Here, it is further proposed that there is a possibility of latency in SARS-CoV2 virus infection if it is acting through TG which is the main site for other viruses that become latent.